Chironomidae bloodworms larvae as aquatic amphibian food. Issue 3 (17th February 2014) - Sharifian Fard, Mojdeh; Pasmans, Frank; Adriaensen, Connie; Laing, Gijs Du; Janssens, Geert Paul Jules; Martel, An
<x xml:space="preserve">Abstract</x> Different species of chironomids larvae (Diptera: Chironomidae) so‐called bloodworms are widely distributed in the sediments of all types of freshwater habitats and considered as an important food source for amphibians. In our study, three species of Chironomidae (Baeotendipes noctivagus, Benthalia dissidens, and Chironomus riparius) were identified in 23 samples of larvae from Belgium, Poland, Russia, and Ukraine provided by a distributor in Belgium. We evaluated the suitability of these samples as amphibian food based on four different aspects: the likelihood of amphibian pathogens spreading, risk of heavy metal accumulation in amphibians, nutritive value, and risk of spreading of zoonotic bacteria (Salmonella, Campylobacter, and ESBL producing Enterobacteriaceae). We found neither zoonotic bacteria nor the amphibian pathogens Ranavirus and Batrachochytrium dendrobatidis in these samples. Our data showed that among the five heavy metals tested (Hg, Cu, Cd, Pb, and Zn), the excess level of Pb in two samples and low content of Zn in four samples implicated potential risk of Pb accumulation and Zn inadequacy. Proximate nutritional analysis revealed that, chironomidae larvae are consistently high in protein but more variable in lipid content. Accordingly, variations in the lipid: protein ratio can affect the amount and pathway of energy supply to the amphibians. Our study indicated although environmentally‐collected chironomids larvae may not be vectors of specific pathogens, they can be associated with nutritional imbalances and may also result in Pb bioaccumulation and Zn inadequacy in amphibians. Chironomidae larvae may thus not be recommended as single diet item for amphibians. Zoo Biol. 33:221–227, 2014. © 2014 Wiley Periodicals, Inc.